2005
DOI: 10.1183/09059180.05.00009603
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication with the patient: FIGURE 1.

Abstract: The chronic and slowly progressive nature of chronic obstructive pulmonary disease (COPD) can create difficulties in effective communication between healthcare provider and patient. Such barriers, which include the personal beliefs of both caregiver and patient, need to be understood and addressed if the aims of the consultation are to be met.Patients with COPD may feel guilty, depressed and angry about their condition. Many patients with COPD are elderly and/or from lower socio-economic groups, both of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…This study demonstrates that involving patients in decisions about their care has a statistically significant effect on their satisfaction. This has been demonstrated by several studies and is a key attribute of the patient-centered consultation method [15][16][17]. Involving the patient does not mean all decisions must be 'ratified' by the patient but it does mean that he should be fully aware of the reasons for the decision and the available options.…”
Section: Involving the Patient In Decisions About The Carementioning
confidence: 99%
“…This study demonstrates that involving patients in decisions about their care has a statistically significant effect on their satisfaction. This has been demonstrated by several studies and is a key attribute of the patient-centered consultation method [15][16][17]. Involving the patient does not mean all decisions must be 'ratified' by the patient but it does mean that he should be fully aware of the reasons for the decision and the available options.…”
Section: Involving the Patient In Decisions About The Carementioning
confidence: 99%
“…Furthermore, multivariate analysis demonstrated that CAT and breathlessness were more significant explanatory variables than the frequency of disease worsening or employment status. These two measures have been emphasized in the symptom assessment of COPD patients following the revision of GOLD 2011 [3]. It has been reported that CAT can appropriately evaluate disease worsening [20] and progress in rehabilitation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this expected increase in the number of older adults, it is necessary to maintain good communication with elderly patients to continue the treatment of chronic diseases. Humanistic approach, respect, and people-focused attitude are critical for good communication with COPD patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…ersjournals.com) and the number of downloaded ERR articles worldwide [3]. As an illustration, the top 10 most read articles since November 2010 have totalled more than 76,458 full-text downloads [4][5][6][7][8][9][10][11][12][13]. Together, the recently launched ERS publications app, the ERR website optimised for smartphones and tablets, the social bookmarks for Twitter and Facebook, and the twitter feed @ERSpublications, contribute to increasing the visibility of ERR articles.…”
mentioning
confidence: 99%